Investigating potential rooftop solar energy generated by Leased Federal Airports in Australia: Framework and implications. (September 2021) - Teofilo, Athenee; Sun, Qian (Chayn); Radosevic, Nenad; Tao, Yaguang; Iringan, Jerome; Liu, Chengyang
Abstract: Australia is facing an energy crisis, yet the solar resource is still underutilized. Government's support to small-scale residential solar photovoltaic (PV) systems undermines large-scale rooftop PV systems which are relatively overlooked, and their fully potential remains unexplored. This paper addresses the importance of implementing large-scale rooftop PV systems at airports precinct for energy planning and policy making. This paper aims to investigate the potential of electricity production of rooftop solar PV at 21 Leased Federal Airports (LFAs) in Australia. Specifically, we demonstrated a reproducible methodological framework including: (i) a low-cost data collection of 3D rooftop, (ii) a user-friendly solar radiation modeling in GIS, and (iii) accurate estimation of electricity potential from large-scale airport rooftop solar PV arrays. In addition, a comparison of rooftop solar PV energy productions between the LFAs and a local government area, City of Greater Bendigo, was conducted. The results show that estimated annual electricity potential from large-scale rooftop PV systems at 21 LFAs is 466.68 GWh, and nearly 10 times greater than the annual electricity generated with nearly 17, 000 installed residential solar rooftop PV panels in the local government area. If the potential area of LFAs rooftops, currently 2.61 km 2 in total, were considered for solar PV, Australia could mitigate the energy crisis significantly to supply the equivalent of 136, 000 homes and offset 151.6 kt of GHG emission annually. The outcome of this study not only opens the possibilities for more large-scale solar rooftop PV projects but also aids the authorities in their drive to lessen carbon emissions in the country. Highlights: Airport buildings are ideal place for large-scale solar photovoltaic but overlooked in Australia. Low-cost GIS-based framework for investigating large-scale solar potential of airport rooftops. High electricity yield by rooftop solar PV installation at 21 Leased Federal Airports in Australia. Significant greenhouse gas offset from producing electricity by airport solar photovoltaic.